Political elite theory in contemporary American perspective - Shakir , Rana mawlood (Tikrit Journal For Political Science, 2024)
A The political elite in contemporary Western democratic societies is the main catalyst for popular awareness to determine the nature of their political choices, and how to obtain and preserve their rights and ensure their continuity. In the American political perspective, this elite has far outperformed its Western European counterpart, especially since liberal democracy has been able to form a unique leadership elite in Thinking and political action, to become the rational force to support the requirements and rights of the nation and balance it with the orientations of governance and decision-makers, by employing their cognitive and mental perception and transforming it into effective influences between both parties to ensure the maintenance of rights and stability in its various fields.